Collaborative Governance dalam Program Pelayanan Instruktur Senam Gratis di Kabupaten Pamekasan - Nurul Aini Pradika; Nafi’ah, Binti Azizatun (PUBLIKA : Jurnal Ilmu Administrasi Publik, 2025)
This study aims to describe the collaboration undertaken by the Dinas Kepemudaan, Olahraga dan Pariwisata (Disporapar), with various stakeholders in supporting a healthy lifestyle through the Pelayanan Instruktur Senam Gratis(PING) program. The research uses a qualitative descriptive approach, with data collected through observation and in-depth interviews with key stakeholders, including local government officials, aerobics instructors, partner sub-districts, and community members as service recipients. The findings reveal that the PING program is implemented through a collaborative governance approach involving public, private, and community actors. The collaboration process includes principal engagement, shared motivation, and capacity for joint action. The program has shown effective collaboration; however, there are still challenges related to information dissemination and administrative systems. The study recommends improving outreach strategies and administrative processes.